Cardiac Implantable Electronic Device (CIEDs) for Heart Failure in Indonesia: We Have to be More Selective - Ardian Rizal (Heart Science Journal, 2020)
Cardiac Implantable Electronic Device (CIEDs) had been recommended as an integral part of heart failure management. Despite clear benefits on CIEDs itself, the rate of therapy penetration in Indonesia is still very low. Many contributing factors had been identified, they are lack of physician awareness, lack of referral, and mismatch between national insurance reimbursement and the cost of therapy. We focussed on talking about selective patient selection as one of the most feasible solutions to this problem.